Arginase Pathway in Acute Retina and Brain Injury: Therapeutic Opportunities and Unexplored Avenues - Fouda, Abdelrahman Y.; Eldahshan, Wael; Narayanan, S. Priya; Caldwell, R. William; Caldwell, Ruth B. (Frontiers in Pharmacology, 2020)
Ischemic retinopathies represent a major cause of visual impairment and blindness. They include diabetic retinopathy (DR), acute glaucoma, retinopathy of prematurity (ROP) and central (or branch) retinal artery occlusion (CRAO). These conditions share in common an initial period of ischemia or reduced blood supply to the retinal tissue that eventually leads to neuronal degeneration. Similarly, acute brain injury from ischemia or trauma leads to neurodegeneration and can have devastating consequences in patients with stroke or traumatic brain injury. In all of these conditions, current treatment strategies are limited by their lack of effectiveness, adverse effects or short time window for administration. Therefore, there is a great need to identify new therapies for acute central nervous system (CNS) injury. In this brief review article, we focus on the pathway of the arginase enzyme as a novel therapeutic target for acute CNS injury. We review the recent work on the role of arginase enzyme and its downstream components in neuroprotection in both retina and brain acute injury models. Delineating the similarities and differences between the role of arginase in the retina and brain neurodegeneration will allow for better understanding of the role of arginase in CNS disorders. This will also facilitate repurposing the arginase pathway as a new therapeutic target in both retina and brain diseases.